Clinical application of the fracture risk assessment tool in the general population and its correlation with bone turnover markers - Yang, Zhi; Xuan, Shu; Li, Weihong; Hu, Wan; Tu, Ping; Duan, Peng (Frontiers in Pharmacology, 2023)
Objective: To compare the risk of osteoporotic fractures between the urban and urban-rural fringe populations in southern China and to explore the effect of bone turnover markers on fracture risk. Methods: Epidemiological investigations were conducted in the urban and urban-rural fringe areas of southern China in June 2018. Residents aged 40 years and over who signed informed consent forms were included. Physical examination and questionnaire collection were completed. Bone turnover markers (BTMs) including osteocalcin (OC) and beta cross-linked C-telopeptide of type 1 collagen (β-CTX) were tested. Bone mineral density (BMD) of the femoral neck and lumbar vertebrae 1–4 were measured using dual energy X-ray absorptiometry. Fracture risk assessment tool (FRAX) values were calculated to show the probability of major osteoporotic fracture (PMOF) and probability of hip fracture (PHF) over the next 10 years. Results: A total of 1,051 participants were included in this study, including 553 in the urban areas and 498 in the urban-rural fringe areas. The average PMOF and PHF were 3.4 (2.3–5.4) % and .6 (.3–1.5) %, respectively. Compared with that in the urban populations, the femoral neck BMD in the urban-rural fringe populations was lower and FRAX values were generally higher, especially for women. FRAX values in various populations were mainly negatively correlated with lumbar and femoral neck BMD and were positively correlated with β-CTX; meanwhile, only PHF was negatively correlated with OC. After adjusting for sex, elevated β-CTX levels significantly increased the risk of high PMOF in various populations and increased the risk of high PHF in the urban-rural fringe populations. In particular, the risks of increased PMOF and PHF could increase by as much as 33 times and 19.5 times, respectively, in the urban-rural fringe areas. Conclusion: The urban-rural fringe populations in Southern China may be at risk of osteoporotic fracture. In addition to being related to BMD, the FRAX value also correlates with some BTMs. Combining FRAX with BMD, and BTMs may better predict the fracture risk.